Pengaruh Otago Exercise Programme Terhadap Rentang Gerak Sendi Pada Lanjut Usia - Erna Kurnianingsih (Jurnal Keterapian Fisik, 2017)
Abstract: Otago Exercise Programme-Range of Motion - Elderly. Subject’s characteristic of this study are elderly with a different style of dressing and they prefer barefoot when doing exercises. Otago Exercise Programme (OEP) is one of exercise type to reduce fall risk in elderly. OEP was an important exercise to prevent fall risk. This programme have been delivered in west country and it had improved the elder people’s balance skill. The aim of this study is to analyse the effect of OEP to range of motion of the elderly. This is a quasi-experimental research with a nonrandomized control group pretest posttest design. The subjects of this study are 24 elderly of treated group and 24 elderly of control group. Subject’s inclusion criteria are: healthy female elderly of local government social institution care for the elderly in Sleman Yogyakarta with the age of 60-75 years old. The subject’s range of motion of knee flexion, plantar flexion and dorsi flexion of the ankle range of motion were measured by goniometer. Subject on treated group are given Otago Exercise Programme 3 times a week, 30 minutes each session for 8 weeks. Both subject were being measured their Range of Motion before and after research. Independent t-test was used to compared the result. There is no differences between ankle dorsi and plantar flexion range of motion before and after research on both treated or control group (p<0,05). OEP doesn’t have impact on range of motion of the elderly.